Common functionally important motions of the nucleotide‐binding domain of Hsp70. Issue 2 (18th December 2014) - Gołaś, Ewa I.; Czaplewski, Cezary; Scheraga, Harold A.; Liwo, Adam
ABSTRACT The 70 kDa heat shock proteins (Hsp70) are a family of molecular chaperones involved in protein folding, aggregate prevention, and protein disaggregation. They consist of the substrate‐binding domain (SBD) that binds client substrates, and the nucleotide‐binding domain (NBD), whose cycles of nucleotide hydrolysis and exchange underpin the activity of the chaperone. To characterize the structure–function relationships that link the binding state of the NBD to its conformational behavior, we analyzed the dynamics of the NBD of the Hsp70 chaperone from Bos taurus (PDB 3C7N:B) by all‐atom canonical molecular dynamics simulations. It was found that essential motions within the NBD fall into three major classes: the mutual class, reflecting tendencies common to all binding states, and the ADP‐ and ATP‐unique classes, which reflect conformational trends that are unique to either the ADP‐ or ATP‐bound states, respectively. "Mutual" class motions generally describe "in‐plane" and/or "out‐of‐plane" (scissor‐like) rotation of the subdomains within the NBD. This result is consistent with experimental nuclear magnetic resonance data on the NBD. The "unique" class motions target specific regions on the NBD, usually surface loops or sites involved in nucleotide binding and are, therefore, expected to be involved in allostery and signal transmission. For all classes, and especially for those of the "unique" type, regions of enhanced mobility can be identified; these are termed "hot spots, " and their locations generally parallel those found by NMR spectroscopy. The presence of magnesium and potassium cations in the nucleotide‐binding pocket was also found to influence the dynamics of the NBD significantly. Proteins 2015; 83:282–299. © 2014 Wiley Periodicals, Inc.